1996
DOI: 10.1246/bcsj.69.1869
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Properties of Titanium-Including Complex, Tris(tetramethyltetrathiafulvalene) Di-μ-fluoro-bis[tetrafluorotitanate(IV)], (TMTTF)3Ti2F10

Abstract: A novel molecular complex of tetramethyltetrathiafulvalene (TMTTF) was prepared by the treatment with TiF4. The X-ray analysis reveals the exsistence of a trimer of TMTTF’s and a Ti2F102− anion in a triclinic unit cell of the dimension; a = 10.934(3), b = 12.798(2), c = 8.000(1) Å, α = 103.86(1), β = 107.08(2), γ = 75.02(2)°. All the molecular planes of TMTTF are nearly parallel. The trimers stack parallel to the a axis, and the intertrimer interaction is estimated to be weak. A semiconductive behavior with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 14 publications
2
10
0
Order By: Relevance
“…It should also be mentioned that the earlier reported examples of dicationic (TMTTF) 3 2+ trimers showed either rotated arrangements of TMTTF moieties or shifted moieties (analogous to that with (TMTTF) 3 +• ). ,, The structural features of the former indicate that the larger fractions of charge are residing on the side moieties (similar to that observed in the current work), while structural and FT-IR characterizations of the latter revealed that the charge is located mostly on the central moiety. , To rationalize charge distributions in the mono- and dicationic trimers, we first considered a simplified molecular-orbital (MO) diagram of these associations. The MO LCAO model of the π-stacked trimers suggests that the interaction of (occupied or semioccupied) frontier orbitals of three TMTTF monomers results in the formation of bonding (B), nonbonding (NB), and antibonding (AB) orbitals of the complex.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…It should also be mentioned that the earlier reported examples of dicationic (TMTTF) 3 2+ trimers showed either rotated arrangements of TMTTF moieties or shifted moieties (analogous to that with (TMTTF) 3 +• ). ,, The structural features of the former indicate that the larger fractions of charge are residing on the side moieties (similar to that observed in the current work), while structural and FT-IR characterizations of the latter revealed that the charge is located mostly on the central moiety. , To rationalize charge distributions in the mono- and dicationic trimers, we first considered a simplified molecular-orbital (MO) diagram of these associations. The MO LCAO model of the π-stacked trimers suggests that the interaction of (occupied or semioccupied) frontier orbitals of three TMTTF monomers results in the formation of bonding (B), nonbonding (NB), and antibonding (AB) orbitals of the complex.…”
Section: Resultssupporting
confidence: 73%
“…The (TMTTF) 3 2+ associations are capped on both sides with Br 6 CAR – anions, which provide clear separation between trimeric units with no close intertrimer contacts between TMTTF moieties (in contrast to the published structures in which (TMTTF) 3 2+ units represented more or less distinct parts of the infinite TMTTF stacks , ). The stoichiometry of the salt indicates a 2+ charge for each TMTTF trimer.…”
Section: Resultsmentioning
confidence: 94%
“…The ([Ti 6 F 27 ] 3– ) ∞ anion represents the first example of a 3-D framework built of TiF 6 octahedra. To date only examples of 0-D ([Ti 2 F 10 ] 2– , , [Ti 2 F 11 ] 3– , [Ti 4 F 18 ] 2– , [Ti 4 F 19 ] 3– , [Ti 4 F 20 ] 4– , [Ti 5 F 23 ] 3– , [Ti 8 F 36 ] 4– , and [Ti 10 F 45 ] 5– ), 1-D {([TiF 5 ] − ) ∞ , ([Ti 2 F 9 ] − ) ∞ , , ([Ti 3 F 13 ] − ) ∞ , ([Ti 7 F 30 ] 2– ) ∞ , and ([Ti 9 F 38 ] 2– ) ∞ }, and 2-D {([Ti 8 F 33 ] − ) ∞ } , geometries have been known.…”
Section: Discussionmentioning
confidence: 99%
“… , Almost three-quarters of the characterized compounds are hexafluoridotitanate­(IV) ([TiF 6 ] 2– ) salts. Other oligomeric fluoridotitanate­(IV) anions with 0-D geometry are presented by [Ti 2 F 10 ] 2– , , [Ti 2 F 11 ] 3– , [Ti 4 F 18 ] 2– , [Ti 4 F 19 ] 3– , [Ti 4 F 20 ] 4– , [Ti 5 F 23 ] 3– , [Ti 8 F 36 ] 4– , and [Ti 10 F 45 ] 5– . Known polymeric fluoridotitanate­(IV) anions include five 1-D examples {([TiF 5 ] − ) ∞ , ([Ti 2 F 9 ] − ) ∞ , , ([Ti 3 F 13 ] − ) ∞ , ([Ti 7 F 30 ] 2– ) ∞ , and ([Ti 9 F 38 ] 2– ) ∞ } and two 2-D examples {two modifications of ([Ti 8 F 33 ] − ) ∞ anion , }.…”
Section: Introductionmentioning
confidence: 99%
“…In the solid state these units can remain isolated, leading to trivial hexafluoridotitanate(IV) salts, or they can be linked by sharing fluorine ions, yielding larger oligomeric (0‐D geometry) or polymeric (1‐D, 2‐D and 3‐D) anions. So far, there are 18 structurally characterized fluoridotitanate(IV) anions: oligomeric [TiF 6 ] 2– , [Ti 2 F 10 ] 2– ,, [Ti 2 F 11 ] 3– , [Ti 4 F 18 ] 2– , [Ti 4 F 19 ] 3– , [Ti 4 F 20 ] 4– , [Ti 5 F 23 ] 3– , [Ti 8 F 36 ] 4– , [Ti 10 F 45 ] 5– , and polymeric ([TiF 5 ] – ) ∞ , ([Ti 2 F 9 ] – ) ∞ ,, , ([Ti 3 F 13 ] – ) ∞ , ([Ti 4 F 19 ] 3– ) ∞ , ([Ti 6 F 27 ] 3– ) ∞ , ([Ti 7 F 30 ] 2– ) ∞ , ([Ti 9 F 38 ] 2– ) ∞ , and two modifications of the ([Ti 8 F 33 ] – ) ∞ anion , . The geometries of the various anions were determined with X‐ray experiments on single crystals of pure inorganic and/or hybrid compounds.…”
Section: Introductionmentioning
confidence: 99%